Upaya Meningkatkan Kemampuan Motorik Halus Melalui Meronce Denganmedia Pelepah Pepayapada Anak Kelompok B Semester I Di TK Dharma Wanita Sonokidul 2 Kunduran Blora Tahun 2015/2016 - NGATMINI, SRI; , Drs. M. Yahya, M.Si (2015)
Thesis PG-PAUD the Faculty of Education, University of Muhammadiyah Surakarta, September 2015 The development of early childhood education could include the development of fine motor skills. Fine motor that will be provided for early childhood is the developmental control of body movement through meronce. This research aims to improve children's fine motor skills through activities meronce with papaya midrib media in children in group B TK Dharma Wanita Sonokidul 2 Kunduran Blora The study, obtained before the improvement was held class (Pre cycle) the child is able or completed by (25%), children who have not been able to 74.682%. Having held research increased in the first cycle of the child who is able to accomplish the task without the help of rising to 54.843%. children who have not been able to 45.157% because the results have not been reached or exceeded an indicator of success, then the researchers make improvements back on the second cycle and the result is a child who would finish meronce activity increases. For children who are able 85%, children who have not been able to complete tasks 15% the result exceeds the indicator of success is 80%. The conclusion of this study successfully. This success depends as learning to use the method of administration tasks and media used by teachers varied.